P–415 Clinical and In Vitro Fertilization laboratory parameters that contribute to clinical miscarriage after single euploid embryo transfer. (6th August 2021) - Nogale. Barrios, M D C; García-Velasco, J A; Cruz, M; Frutos, S D; Martínez, E M; Gaytán, M; Ariza, M; Bronet, F
Abstract: Study question: To investigate which factors, excluding embryo aneuploidies, are associated with miscarriage in patients who have undergone a single euploid blastocyst transfer. Summary answer: Miscarriage was related to the body mass index (BMI), the type of cycle and the thickness of the endometrium. What is known already: Preimplantation genetic testing for aneuploidies (PGT-A) is widely used in-vitro fertilization (IVF) to select euploid embryos. Several studies have shown that embryo aneuploidy is the main contributing factor for IVF failure, reinforcing the relevance of PGT-A as a method to select chromosomally normal embryos. A recent meta-analysis confirmed that patients undergoing PGT-A have a lower miscarriage rate than women that conceived naturally (9% vs 28%, respectively). Even though most of the studies show that PGT-A significantly reduces miscarriage rate, still some women do lose their pregnancies. We investigated which other reasons may be related to this early pregnancy loss. Study design, size, duration: Retrospective, observational, and multicenter study of 6910 patients undergoing single euploid blastocyst transfer after PGT-A from January 2017 to December 2019 in our institution. Several laboratory and clinic variables were analyzed to study the effect of these variables on the miscarriage rate Participants/materials, setting, methods: Indications for PGT-A were advanced maternal age, implantation failure, recurrent pregnancy loss and male factor. Embryos were cultured 5% O2 concentration and 6.5% CO2 concentration. Trophectoderm biopsy was performed on day 5/6 of development and analyzed through Next Generation Sequencing (NGS); embryos were vitrified until transfer was performed. Single euploid embryo transfer was performed in all cases. We performed a multivariate regression analysis to compare the different variables and search for there are significant differences. Main results and the role of chance: We studied a total of 6910 patients undergoing PGT-A to describe which factors, excluding embryo aneuploidies, were correlated with miscarriage in patients who underwent single thawed euploid embryo transfer. When considering embryo morphology (embryo grading, quality of inner cell and quality of trophectoderm), we did not find differences in miscarriage rate among groups (high quality= 15.9%; normal quality= 14.3%; low quality= 15.0%; poor quality= 14.8%) p = 0.833. BMI was significantly associated with miscarriage rate (odds ratio [OD] 1.04; 95% confidence interval [CI], 1.012–1–076 p = 0.006) and miscarriage rate. We observed a weak association between endometrial thickness and miscarriage rate ([OD] 0.65; 95%, 0.528–0.778 p = 0.04) and also between type of endometrial preparation (natural cycle or hormone replacement cycle) ([OD] 0.77; 95%, 0.528–0.778) p = 0.04. Body mass index, according to our findings, was the main variable correlated with miscarriage rate. We did not find any association with the other variables studied (biopsy day, maternal age, male age, duration infertility, cycle length, previous miscarriage, previous live birth, previous cycles IVF, endometrial pattern and diagnosis). Limitations, reasons for caution: The retrospective study design limits the generalization of our results but offers a good insight to be validated in prospective trials. Wider implications of the findings: According to our findings, BMI, endometrial thickness the day of the embryo transfer, and the type of endometrial preparation should be considered when transferring an euploid blastocyst. Trial registration number: NO APLICA